Peruvian fishmeal industry resilience to El Niño Southern Oscillation (ENSO) events: implications for industry structure - Leiva Lanza, Paul (Kansas State University, 2018)
With the recent increase in record-breaking weather events and the inherent susceptibility of the fishmeal industry to temperature fluctuations, the industry dynamics and sustainability of the Peruvian fishmeal sector has gained renewed attention. Among important causes of concern are the cyclical impact of El Niño Southern Oscillation (ENSO) events on productivity and profitability of fishmeal producing firms, long-term structural changes in the industry, and resulting socio-economic consequences. Although distinct risk management strategies have been implemented by industry players and a range of policy initiatives have been introduced by the government over the years, the firms in the Peruvian fishmeal industry remain highly susceptible to the effects of ENSO events. The increased frequency and magnitude of ENSO events over the past decade has forced relatively less resilient firms out of business and has been accompanied by an observable trend towards increased industry concentration. While there is a potential for efficiency gains and economies of scale from increased concentration, policy makers and industry players have concerns about negative social implications from declining numbers of small and medium firms and shifting competitive dynamics in the industry. As a result, policy-makers and industry stakeholders are in the continuous search for effective strategies and mechanisms for enhancing the resilience of individual fishmeal producers and the overall industry to the effects of ENSO events. The objective of this study is to expand the understanding of factors that affect the resilience of firms to ENSO events in the Peruvian fishmeal industry. The analysis is based on a panel database that combines information from the Peruvian Instituto Nacional de Estadística e Informática (Statistics Institute), Aduanet (Peruvian Customs website), and the Oceanic Niño Index (ONI). The objective is to identify firm characteristics and factors that can potentially enhance the resilience of a firm to the negative impacts of ENSO events. The specific period of study covers the ENSO event that lasted from July 2009 to April 2010. The resilience of individual firms is measured by applying system resilience framework proposed by Barroso et al. (2015). Subsequently, the effect of a range of characteristics on firm resilience is estimated using a fractional response logit method. Among key parameters of interest are the estimated effects of size, experience, location, and participation in government support programs. The results indicate positive relationship between resilience and experience, diversification, access to government subsidy programs, and share of imported inputs. The results also indicate a negative effect of firm size on resilience to ENSO events. The industry and policy implications of the findings are discussed, while highlighting the number of methodological limitations. The overall contribution of this study is twofold. First it presents an application of resilience triangle approach to measuring firm resilience in the context of Peruvian fishmeal industry. Second, it provides new insights on the factors affecting firm resilience to the negative impact of ENSO events. The findings have a potential to inform policy and industry initiatives designed to enhance the industry’s ability to cope with negative consequences of ENSO events.
Keywords: Fishmeal; ENSO; Industry structure; Resilience Framework; Peru